2003
DOI: 10.1079/bjn2003873
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary conjugated linoleic acid on fatty acid composition and cholesterol content of hen egg yolks

Abstract: The main objectives of the present study were to determine the effect of dietary conjugated linoleic acid (CLA) isomers on the fatty acid composition and cholesterol content of egg-yolk lipids. Forty-five 25-week-old laying hens were randomly distributed into five groups of nine hens each and maintained in individual laying cages, throughout 12 weeks of the experiment. They were assigned to the five treatments that consisted of commercial layer diets containing 0, 5, 10, 15 or 20 g pure CLA/kg. Feed intake of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 47 publications
8
28
4
Order By: Relevance
“…SFA and PUFA was increased (P<0.01) by dietary CLA compared with the control group (0% CLA), whereas the concentration of MUFA decreased (P<0.01). These results are in accordance with the findings of Chamruspollert and Sell (1999) and Szymczyk et al (2003). …”
Section: Resultssupporting
confidence: 83%
“…SFA and PUFA was increased (P<0.01) by dietary CLA compared with the control group (0% CLA), whereas the concentration of MUFA decreased (P<0.01). These results are in accordance with the findings of Chamruspollert and Sell (1999) and Szymczyk et al (2003). …”
Section: Resultssupporting
confidence: 83%
“…Garg et al (1988) demonstrated that both linseed oil and fish oil diets inhibited delta-9 desaturase activity in rat liver microsomes. investigators (Yang et al 2002;Szymczyk & Pisulewski, 2003). Increased levels of linoleic and α-linolenic acids in the fat added to the diet significantly increased the concentration of linoleic, α-linolenic, and docosahexaenoic (DHA) in white and brown eggs, although the levels of arachidonic and docosapentaenoic acids decreased during the AF-SO dietary period.…”
Section: Egg Fat and Fatty Acid Contentsmentioning
confidence: 99%
“…In recent years linseed cultivars containing oil low in α-linolenic acid and rich in linoleic acid have been introduced (Borowiec et al, 2001). Enrichment of laying hen diets with conjugated linoleic acid has been reported to decrease the yolk weight and cholesterol content of eggs (Szymczyk and Pisulewski, 2003). The aim of this study was to compare the effects of feeding laying hens with seeds of regular or modified low-α-linolenic acid cultivars of linseed on laying performance and cholesterol content in eggs.…”
Section: Introductionmentioning
confidence: 99%
“…The egg is considered an ideal target for dietary modification leading to the development of functional food (Szymczyk and Pisulewski, 2003). Enrichment of laying hen diets with regular full-fat linseeds beneficially affected the functional value of eggs due to an increased content of n-3 polyunsaturated fatty acids (PUFA) (Scheideler and Froning, 1996;Van Elswyk, 1997).…”
Section: Introductionmentioning
confidence: 99%